AIA Vitality Women’s 10K Event Management by AIA Indonesia in an Effort to Increase Indonesian Women’s Health Awareness - Sari, Fany Puspita; Apriliani, Riski (Jogjakarta Communication Conference (JCC), 2025)
AIA Vitality Women's 10K is a running event organized specifically for women as a commemoration of International Women's Day. This event was held by the insurance company AIA Indonesia in Solo City which was attended by approximately 1000 participants with the majority of women. This research is intended to find out how the AIA vitality women's 10k event management strategy as an effort to increase women's health awareness in the field of sports. This research uses a descriptive qualitative approach method. The data sources used are primary data by conducting interviews with participants and organizers, and secondary data by conducting content analysis through social media instagram. The data analysis technique used in this research is data reduction, data presentation, and conclusion drawing. To ensure accurate data, this research uses data triangulation as part of obtaining data that can be accounted for.